1996
DOI: 10.1172/jci118733
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor acetylhydrolase deficiency. A missense mutation near the active site of an anti-inflammatory phospholipase.

Abstract: Deficiency of plasma platelet-activating factor (PAF) acetylhydrolase is an autosomal recessive syndrome that has been associated with severe asthma in Japanese children. Acquired deficiency has been described in several human diseases usually associated with severe inflammation. PAF acetylhydrolase catalyzes the degradation of PAF and related phospholipids, which have proinflammatory, allergic, and prothrombotic properties. Thus, a deficiency in the degradation of these lipids should increase the susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
184
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(201 citation statements)
references
References 42 publications
13
184
0
4
Order By: Relevance
“…Concerning platelet membrane glycoproteins, it has been reported that genetic polymorphisms of GPIa, 10 GPIba, 11 GPIIIa 12,13 and GPVI 14 influence the efficacy of aspirin or platelet responsiveness. Furthermore, Halushka et al 15 reported the association of platelet aggregation with genetic mutation of COX-1, Papafili et al 16 the association with genetic mutation of COX-2, Higuchi et al 17 the association with genetic mutation of TXA 2 receptors (TP), Stafforini et al 18 the association with genetic mutation of platelet activating factor acetylhydrolase (PAFAH) and Undas et al 19 the association with genetic mutation of coagulation factor XIII (FXIII).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning platelet membrane glycoproteins, it has been reported that genetic polymorphisms of GPIa, 10 GPIba, 11 GPIIIa 12,13 and GPVI 14 influence the efficacy of aspirin or platelet responsiveness. Furthermore, Halushka et al 15 reported the association of platelet aggregation with genetic mutation of COX-1, Papafili et al 16 the association with genetic mutation of COX-2, Higuchi et al 17 the association with genetic mutation of TXA 2 receptors (TP), Stafforini et al 18 the association with genetic mutation of platelet activating factor acetylhydrolase (PAFAH) and Undas et al 19 the association with genetic mutation of coagulation factor XIII (FXIII).…”
Section: Introductionmentioning
confidence: 99%
“…The Val279Phe (V279F) homogygous mutation (279FF) is the only polymorphism theoretically resulting in no circulating gene product of Lp-PLA2. 9, 10 The prevalence of 279FF was reported to be 0.4%, 1.2%, and 3% in the Chinese, Korean, and Japanese populations, respectively, 11-13 but this variant is rare in non-Asian populations. 14 In a recent meta-analysis including 79,036 participants in 32 prospective studies, Lp-PLA2 activity and mass each showed continuous associations with risk of CAD, similar in magnitude to that with non-high-density lipoprotein cholesterol and systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…9, 10 Jang et al found that the V279F variant in the PLA2G7 gene led to significant loss of enzyme activity in heterozygous subjects and no appreciable enzyme activity in homozygous subjects. The mechanism of the deficiencies of plasma Lp-PLA2 activity were suggested to be due to a loss-of-function mutation (V279F, exon 9, position 994; G3T; G>T) in the Lp-PLA2 gene, because Val-279 conserved in plasma Lp-PLA2 lies between the active site Ser-273 and Asp-296 residues in a region that is critical for proper folding of the enzyme.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Stafforini et al 19 mapped the PLA2G7 gene (PAFAH) to chromosome 6p21.1-p12 and found that it contains 12 exons. Deficiency of plasma platelet-activating factor resulting from a missense mutation (Val279-Phe) in exon 9 of the gene has been described.…”
mentioning
confidence: 99%